Comprehensive insights into the occurrence and toxicological issues of nodularins. (January 2021) - Chen, Guoliang; Wang, Linping; Wang, Mingxing; Hu, Tingzhang
Abstract: The occurrence of cyanobacterial toxins is being increasingly reported. Nodularins (NODs) are one of the cyanotoxins group mainly produced by Nodularia spumigena throughout the world. NODs may exert adverse effects on animal and human health, and NOD-R variant is the most widely investigated. However, research focused on them is still limited. In order to understand the realistic risk well, the aim of this review is to compile the available information in the scientific literature regarding NODs, including their sources, distribution, structural characteristics, physicochemical properties, biosynthesis and degradation, adverse effects in vitro and vivo, and toxicokinetics. More data is urgently needed to integrate the cumulative or synergistic effects of NODs on different species and various cells to better understand, anticipate and aggressively manage their potential toxicity after both short- and long-term exposure in ecosystem, and to minimize or prevent the adverse effects on human health, environment and the economy. Highlights: Investigation on the structural characteristics, physicochemical properties and analytical method of NODs. Occurrence of NODs around the world: Sources, poisoning and distribution. The biosynthesis, regulation and degradation of NODs are studied. A potential toxicity of NODs: In vitro and in vivo studies. Evaluation of the toxicokinetics of NODs including cellular uptake, detoxification and toxicity mechanism.